Acceptability and Adherence in a Chemoprevention Trial among Women at Increased Risk for Breast Cancer Attending the Modena Familial Breast and Ovarian Cancer Center (Italy). Issue 1 (17th December 2012) - Razzaboni, Elisabetta; Toss, Angela; Cortesi, Laura; Marchi, Isabella; Sebastiani, Federica; De, Elisabetta; Federico, Massimo
Abstract Chemoprevention for women at risk for breast cancer has been shown to be effective, but in actual practice, women's uptake of chemoprevention has been poor. We explored factors that influence acceptability, adherence, and dropout in the International Breast (Prevention) Intervention Study during our first 3 years of activity at the Modena Familial Breast and Ovarian Cancer Center. We evaluated socio‐demographic characteristics, health status, adherence, and side effect intensity. Semi‐structured interviews analyzed reasons for accepting/refusing/stopping the trial. A total of 471 postmenopausal women were invited to participate, of which 319 declined to participate (68%), 137 accepted to participate (29%), and 15 participants did not make a final decision (3%). Breast cancer‐related worries and trust in our preventive and surveillance programs were the most frequent reasons for accepting. Side effect‐related worry was the most frequent reason for refusing. General practitioners' and family members' opinions played an important role in the decision‐making process. Adherence significantly decreased after a 12‐month follow‐up, but it remained unchanged after 24‐ and 36‐month follow‐ups. Mild/moderate side effects reported by women did not change after 12 months of treatment. Forty percent of women withdrew from the study due to complaints of side effects. We concluded that chemoprevention trials are difficult medical experiments and that the process of deciding about whether or not to participate is based mainly on beliefs and values. This study has important clinical implications. During counselling with prospective participants, it is important to emphasize the potential benefits and to promote an informed choice. How participants make decisions, their belief systems, and their perception of risk are all factors that should be investigated in future research.